EVALUASI PENERAPAN APLIKASI DARLING IBU HAMIL BERBASIS WEB DENGAN METODE UAT - Salsabila, Gusti Naura; Husin, Husin (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2025)
Improving maternal health literacy is a critical priority in efforts to reduce pregnancy-related complications. The DARLING (Data and Information Services for Pregnancy) web-based application was developed as an interactive educational tool for pregnant women. However, the success of such an application is not solely determined by its content, but also by its functionality, system reliability, and user experience. This study employed the User Acceptance Test (UAT) method using the Guttman scale to assess the feasibility of the DARLING application. The study population consisted of 30 pregnant women selected through accidental sampling at Basirih Baru Health Center. The three main variables evaluated were functional aspects, non-functional aspects, and user experience. The data were analyzed using quantitative evaluation methods. The findings showed that all functional indicators received a 100% approval rate, non-functional aspects scored 99.17%, and user experience reached 96.67%. The total score from 12 indicators resulted in an overall feasibility percentage of 98.61%, categorized as “feasible.” The DARLING web-based application was very well received by pregnant women, with a feasibility rate of 98.61%. These findings indicate the application's strong potential as a digital pregnancy education medium. Further research is recommended to evaluate the educational content more thoroughly and to develop additional features that support the specific needs of pregnant women.